2021
DOI: 10.1523/eneuro.0197-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Reduction of the Basic Helix-Loop-Helix Transcription Factor TCF4 Levels in Huntington’s Disease

Abstract: Huntington’s disease (HD) is an inherited neurodegenerative disorder with onset of characteristic motor symptoms at midlife, preceded by subtle cognitive and behavioral disturbances. Transcriptional dysregulation emerges early in the disease course and is considered central to HD pathogenesis. Using wild-type (wt) and HD knock-in mouse striatal cell lines we observed a HD genotype-dependent reduction in the protein levels of transcription factor 4 (TCF4), a member of the basic helix-loop-helix (bHLH) family wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…Western blot analysis revealed that TCF4 protein signal was detectable in both adult human brain and SH-SY5Y cell line (Figure 9). We also detected a possible non-specific signal located between the long and medium TCF4 isoforms in both SH-SY5Y and human brain lysates (Figure 9) since this signal was not detected using other TCF4 antibodies (data not shown) validated by us before (Nurm et al, 2021). Different to SH-SY5Y cell line, we detected all three TCF4 isoform groups in the adult human brain, however expression level of longer TCF4 isoforms was higher compared to the medium and short isoforms (Figure 9; Supplementary Figure S8).…”
Section: Expression Of Tcf4 In Human Tissues Is Highest Around Birthsupporting
confidence: 59%
See 4 more Smart Citations
“…Western blot analysis revealed that TCF4 protein signal was detectable in both adult human brain and SH-SY5Y cell line (Figure 9). We also detected a possible non-specific signal located between the long and medium TCF4 isoforms in both SH-SY5Y and human brain lysates (Figure 9) since this signal was not detected using other TCF4 antibodies (data not shown) validated by us before (Nurm et al, 2021). Different to SH-SY5Y cell line, we detected all three TCF4 isoform groups in the adult human brain, however expression level of longer TCF4 isoforms was higher compared to the medium and short isoforms (Figure 9; Supplementary Figure S8).…”
Section: Expression Of Tcf4 In Human Tissues Is Highest Around Birthsupporting
confidence: 59%
“…The use of numerous alternative 5′ exons results in the expression of many transcripts from the Tcf4 gene, resulting in a variety of TCF4 protein isoforms with different expression patterns between tissue types ( Sepp et al, 2011 ; Nurm et al, 2021 ). We have previously described transcripts from the mouse Tcf4 gene based on available mRNA and expressed sequence tag data from various tissues ( Nurm et al, 2021 ) but characterizing all the isoform encoding transcripts using short-read sequencing is complicated. Here, we did long-read direct RNA-sequencing (RNA-seq) on the Oxford Nanopore Technologies platform from postnatal day 3 (P3) mouse cerebral cortex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations